أثر التحول الرقمي على استراتيجيات إدارة الموارد البشرية "دراسة ميدانية على مديري إدارات الضمان الاجتماعي بمدينة الأبيار" (Comprehensive Journal of Science, 2026)
This study aimed to examine the impact of digital transformation on human resource management strategies in social security institutions, focusing on the departments of El-Abyar City as a case study. The research adopted a descriptive–analytical approach, and primary data were collected using a questionnaire specifically designed for this purpose. The questionnaire was distributed to a sample of 54 managers out of a total population of 60 managers working in the city’s social security departments, yielding a response rate of 91.67%.The results of the statistical analysis, conducted using SPSS software, revealed a positive and statistically significant impact of digital transformation on human resource management strategies overall, with a correlation coefficient of 0.421. The findings also indicated variations in the magnitude of this impact across different domains. The strongest impact was observed in digital recruitment, with a correlation coefficient of 0.382, followed by motivation (0.294), and training and competency development (0.269)